2022
DOI: 10.1002/path.5872
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent FOXK1::GRHL and GPS2::GRHL fusions in trichogerminoma

Abstract: We report 21 cases of trichogerminoma harbouring previously undescribed FOXK1::GRHL1/2 or GPS2::GRHL1/2/3 in‐frame fusion transcripts. Microscopic examination of a preliminary set of five cases revealed well‐delimitated tumours located in the dermis with frequent extension to the subcutaneous tissue. Tumours presented a massive and nodular architecture and consisted of a proliferation of basaloid cells. A biphasic pattern sometime resulting in tumour cell nests (‘cell balls’) was present. Immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Of the 25 TG cases included, 16 cases were reported in a previous study. 2 For the nine previously unreported TG cases, all specimens were sharply circumscribed dermal nodules with frequent extension to the subcutaneous tissue (n = 6/9). The neoplasms displayed a prominent, macro-and micro-nodular architecture and were composed of basophilic epithelial cells.…”
Section: Sstr2a Is a Diagnostic Marker Of Trichogerminomamentioning
confidence: 97%
See 1 more Smart Citation
“…Of the 25 TG cases included, 16 cases were reported in a previous study. 2 For the nine previously unreported TG cases, all specimens were sharply circumscribed dermal nodules with frequent extension to the subcutaneous tissue (n = 6/9). The neoplasms displayed a prominent, macro-and micro-nodular architecture and were composed of basophilic epithelial cells.…”
Section: Sstr2a Is a Diagnostic Marker Of Trichogerminomamentioning
confidence: 97%
“…Since the initial description by Sau et al in 1992, 1 only 52 cases have been reported in the literature. 2 Recently, applying whole transcriptome analysis our group identified recurrent FOXK1::GRHL1/2 and GPS2::GRHL1/2/3 gene fusions in this tumour entity. 2,3 Further investigation of this transcriptomic data set evidenced high level of Somatostatin Receptor 2 (SSTR2) expression in TG.…”
Section: Sstr2a Is a Diagnostic Marker Of Trichogerminomamentioning
confidence: 98%